2013
DOI: 10.1002/mop.27997
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Substrate‐Integrated Waveguide Six‐Port Power Divider/Combiner

Abstract: A wideband six‐port power divider/combiner with suitable coupling flatness is presented in substrate integrated waveguide (SIW) technology. The structure is composed of six ports that are connected to a common central region. By introducing resonating cavities in each port, the bandwidth and reflection of the SIW six‐port device can be enlarged. Unsymmetrical apertures in lateral port arms are used to increase the isolation between the adjacent input and output ports. A six‐port SIW prototype, operating at 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The implementation configurations for all the power dividers are six-port coupler except Liu and Xiao (2017). The coupling length of this work compared with Salehi et al (2013), Venanzoni et al (2015), Liu and Xiao (2017) and Guo et al (2019) are much smaller. However, the fractional bandwidth is higher than the above references.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation configurations for all the power dividers are six-port coupler except Liu and Xiao (2017). The coupling length of this work compared with Salehi et al (2013), Venanzoni et al (2015), Liu and Xiao (2017) and Guo et al (2019) are much smaller. However, the fractional bandwidth is higher than the above references.…”
Section: Resultsmentioning
confidence: 99%
“…Those equations will be used in deriving adjacent ports design impedance equations. Those equations are given below; Equations (16)- (20), where, y i = Y i /Y o is the normalized admittance with respect to Y o .…”
Section: Nodal Equationsmentioning
confidence: 99%
“…Examples of advanced analysis of miniaturized BPDs were highlighted in Reference 17 by etching defect ground structures and composite right‐left handed transmission line as in Reference 12. A number of authors have improved designing BPDs by replacing microstrip lines with waveguides, 18,19 substrate integrated waveguide, 5,20,21 and coplanar waveguide 22 . Some authors have also found that BPDs can be used for unequal output power splitting where, several techniques were reported in the literature to address this issue for 3‐way BPD and 5‐way BPD 23‐27 …”
Section: Introductionmentioning
confidence: 99%
“…Six-port directional couplers are not as common as the four-port counterparts. There are few examples of such devices in the literature [34][35][36]. One reason is that the circuit is quite complex to design.…”
Section: Six-port Directional Couplermentioning
confidence: 99%
“…The return loss can be further improved by adding more steps or irises in the waveguides connecting SMA ports to the core of the device. This approach was used, for example, in [34,35]. However, this increased the final size of the coupler.…”
Section: Six-port Directional Couplermentioning
confidence: 99%